THE EXPERIMENT IN MANUFACTURING A TASK LIGHTING CAP MADE FROM BAMBOO AND SHELLS AS A REPLACEMENT OF MANUFACTURING MATERIALS - Maharani, Ida Ayu Dyah; Karuni, Ni Kadek (Ide dan Dialog Desain Indonesia (Idealog), 2024)
For a variety of indoor activities, humans require artificial lighting, particularly for the activities that need for a task lighting which have focused lighting. Initially, the majority of task lighting design in massive shape and made from manufacturing materials such as metal and frosted glass, which were effective as light reflectors by directing light towards a specific spot in the area that needed to be illuminated. The task lighting cap design has evolved during its development to emphasize the aesthetic qualities of craftsmanship, both in terms of a shape that is no longer massive and using of natural materials that are simpler to procure and manufacture. This frequently results in a change from task lighting to general lighting. In order to restores the right function of task lighting, this experiment was done and the result is products of task lighting with craft aesthetic value that can also be manufactured into effective light reflectors. Bamboo and shells were chosen as the materials that could most closely approximate the quality of metal and frosted glass as light reflectors capable of concentrating lighting at one point in the area in accordance with their function as task lighting through the use of experimental methods from a variety of craft materials that were still possible to form lamp cap. Although bamboo and shell materials, which are made of natural materials, these still have a weak point in lux if compared to manufactured materials cause they have a small amount of absorption, but this can be fixed by changing the lumens of light source.